2016
DOI: 10.1002/ejic.201600471
|View full text |Cite
|
Sign up to set email alerts
|

Bonding Analysis in Homo‐ and Hetero‐Trihalide Species: A Charge Displacement Study

Abstract: The bonding in homo- (X3–) and hetero-trihalides (XYX–), with X = F, Cl, Br, and I; Y = I, has been analyzed through the charge displacement (CD) method, coupled with energy decomposition analysis (EDA). We focus our attention on how the different bond components vary with the distance between the terminal and the central halogen atoms. The results clearly show that all the homo-halide systems X3–feature the same trend of the charge transfer (CT) versus the asymmetry of the three-body system, defined as the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 60 publications
(73 reference statements)
2
12
0
2
Order By: Relevance
“…For the bonding analysis of the II‐I systems, the SAPT0 results are in agreement with the EDA ones, which have been exposed previously, even if at different values of distances . Here we just underline that the CT S obtained spans between –78.80 and –3.58 kcal/mol for II‐I(–2) and II‐I(2) , respectively.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…For the bonding analysis of the II‐I systems, the SAPT0 results are in agreement with the EDA ones, which have been exposed previously, even if at different values of distances . Here we just underline that the CT S obtained spans between –78.80 and –3.58 kcal/mol for II‐I(–2) and II‐I(2) , respectively.…”
Section: Resultssupporting
confidence: 89%
“…It is important to remember here that, according to our previous paper, in the X 3 – systems (X = F, Cl, Br, I), the X – ··· X 2 interaction, in terms of CT CD , does not depend on the nature of X, but only on the geometric arrangement of the three atoms. Now we can generalize the message: even considering different fragments, charged or not, involving halogens or chalcogen atoms, the charge transfer mainly depends on the relative bond elongations.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Prompted by these results, we decomposed the symmetric I 3 − system in I 2 and I − , treating the system as an extreme case of XB. The 3D deformation maps of the electronic density showed that the iodide undergoes charge depletion and the iodine charge accumulation, with a severe polarization of the molecule (Figure 5a) [61]. A large amount of charge is displaced at the isoboundary (CT), 0.400 e, underlining the covalency of the 3c4e bond.…”
Section: Condensed Phasementioning
confidence: 99%